Strategizing Public Diplomacy For Magnetizing Indonesia Tourism - Isnarti, Rika; Putri Rudiany, Novita (Jurnal sosial dan sains, 2024)
Background: Indonesia has an executive section implementing public diplomacy, but does not yet have the characteristics of public diplomacy to be carried out, does not yet have a priority goal on the image that will be achieved by public diplomacy. Tourism is one of Indonesia's strong identities, but a strong image of Indonesian tourism has not yet emerged, which should be a priority, Indonesian tourism is not only limited to many tourist attractions, of course. Public diplomacy can be utilized to support the image of tourism, but it will not reach the optimal target, if the country does not know the instruments and characteristics of its public diplomacy. If Indonesia's public diplomacy is not optimized through a grand strategy, there is no certain modeling, then the great potential in Indonesia's public diplomacy instruments, for example diaspora, culture, and tourism itself, will not be optimally utilized Purpose: This research aims to map the characteristics of Indonesian public diplomacy so as to produce public diplomacy modeling that can be applied with potential instruments to be used, especially in supporting Indonesia's tourism image Methods: The method in this research is based on qualitative data. Results: With the conceptual framework of public diplomacy, interview methods and literature studies, this research found that the characteristics of tourism to be developed in Indonesia are quality and sustainable tourism, with supporting instruments of digital components and Indonesian cultural characteristics. Conclusion: A clear and strategic approach to public diplomacy is essential to improving Indonesia's tourism image. By incorporating digital strategies and engaging both the diaspora and international influencers, Indonesia can better showcase its tourism potential on the global stage.